Study of microcomb threshold power with coupling scaling - Pei-Hsun Wang (Nature Portfolio, 2021)
Abstract We model the generation threshold and conversion efficiency of microcombs by scaling the cavity coupling. With the Lugiato–Lefever equation (LLE), quantitative analysis of threshold is established in the parameter space of pump power and coupling. Considering the large detuning and Kerr-induced phase shift, the threshold power is numerically solved with the minimum at over-coupling, in agreement with that from the traveling wave theory. Furthermore, the coupling dependence on microcomb generation is discussed, providing the accessibility of high-efficient, stable combs (≥ 40%) around the threshold. This work offers universal guidelines for the design of microcombs with low-power and high-efficient operation.